PERAN GURU SOSIOLOGI DALAM PEMBINAAN SIKAP KERUKUNAN ANTAR UMAT BERAGAMA PADA SISWA KELAS X SMA NEGERI 1 - Supriyanto, Agus; Asrianti, Nuraini; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of thid research is â€œthe role of sociology teacher in fostering the harmony of religiousÂ  for student grade X in SMAN 1 Sungai Ambawangâ€.The purpose of this study is to describe how the role of teacher sociology as an educator in fostering attitudes of religious harmony of students, the role of teacher sociology as a teacher in fostering attitudes of religious harmony among students, and the role of teacher sociology as a mentor in fostering attitudes harmony of students of class X SMAN 1 Ambawang. The approach used in this research is qualitative approach with descriptive method. Data collection techniques used are observation techniques, interview guides, and documentation studies, while data collection tools are guidelines for observation, interview guidance, and documentation. The results showed that the role of teachers in fostering of religious harmony has been going well enough it is proven through messages about unity and unity, tolerance framed in bhineka single ika and pancasila, the absence of discriminatory and exemplary. But not yet implemented maximally in because during the learning process there are still students who choose to be solitary by choosing friends from their own ethnic and religious, the lack of knowledge about the student's religion, the negative influence of social media, and the wrong parenting pattern of the parents Keywords: Role of Sociology Teacher, Standing Attitudes, Religious Harmony.